Intrinsic organization of the suprachiasmatic nucleus in the capuchin monkey - Rocha, V. A.; Frazao, R.; Campos, L. M. G.; Mello, P.; Donato, J.; Cruz-Rizzolo, R. J. [UNESP]; Nogueira, M. I.; Pinato, Luciana [UNESP] (Elsevier B.V., 2014)
The suprachiasmatic nucleus (SCN), which is the main circadian biological clock in mammals, is composed of multiple cells that function individually as independent oscillators to express the self-sustained mRNA and protein rhythms of the so-called clock genes. Knowledge regarding the presence and localization of the proteins and neuroactive substances of the SCN are essential for understanding this nucleus and for its successful manipulation. Although there have been advances in the investigation of the intrinsic organization of the SCN in rodents, little information is available in diurnal species, especially in primates. This study, which explores the pattern of expression and localization of PER2 protein in the SCN of capuchin monkey, evaluates aspects of the circadian system that are common to both primates and rodents. Here, we showed that PER2 protein immunoreactivity is higher during the light phase. Additionally, the complex organization of cells that express vasopressin, vasoactive intestinal polypeptide, neuron-specific nuclear protein, calbindin and calretinin in the SCN, as demonstrated by their immunoreactivity, reveals an intricate network that may be related to the similarities and differences reported between rodents and primates in the literature. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biological rhythms; Diurnal monkey; Neuroanatomy; Per2